PENGEMBANGAN MANAJEMEN USAHA SEBAGAI UPAYA PENINGKATAN KINERJA BUMDES - Prasetyo, Deni Widyo (Transpublika Publisher, 2021)
The aim of this research is to find out how the Bung Hatta BUMDes business development strategy is. The research location was carried out at the Bung Hatta BUMDes Gabus Banaran, Tembelang, Jombang. This type of research is qualitative research. Data collection was carried out through several techniques, namely direct observation, interviews, literature studies, and documentation. Data analysis in this study conducted by researchers was more focused during the process in the field along with data collection. The results of the study showed that BUMDes Bung Hatta runs a business in the form of building materials and postal services. The strategies used by BUMDES Bung Hatta include product development strategies, pricing and financial strategies. BUMDes Bung Hatta needs to add more variety to the products being sold. BUMDes Bung Hatta markets products in the online sales medium Shopee. From a financial point of view, BUMDes Bung Hatta continues to improve and optimize the results of existing business profits so that cash flow continues to rotate and the profits obtained can be used for access to the next capital, besides that it also makes monthly reports and is evaluated for all business activities that have been carried out, then seen various problems that have been encountered in running the business.